Autoreduction of cyanoferrate(III) ions in a polymer electrolyte membrane: all solid state electrochemical and spectroscopic investigations - Parthasarathy, Meera; Gopinath, Chinnakonda S.; Pillai, Vijayamohanan K. (Chemistry of Materials, 2006)
The effect of dielectric confinement on proton-coupled electron-transfer behavior and spectroscopic properties of cyanoferrate ions in a polymer electrolyte membrane (Nafion) has been investigated in an ``all-solid-state'' electrochemical cell, using techniques such as cyclic voltammetry, zero current chronopotentiometry, electrochemical impedance, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), UV-visible spectroscopy, X-ray photoelectron spectroscopy (XPS), and electron spin resonance spectroscopy (ESR). From the above investigations, we found that cyanoferrate(III) ions undergo autoreduction in the ionomer matrix, for which a sulfonate-coupled mechanism has been proposed. This report demonstrates the effectiveness of the micellar interface in tuning the redox potential of the confined ions. A systematic analysis of the cyclic voltammetry and impedance data for the [Fe(CN)(6)](4)(-)- containing Nafion membrane enables the estimation of a standard rate constant for [Fe(CN) 6](4-) oxidation, k(o), as 5.44 x 10(-6) cm/s and a diffusion coefficient, D-o, as 1.3 x 10(-12) cm(2)/s. A similar calculation yields a value of 4.8 x 10(-12) cm(2)/s for the diffusion coefficient of protons and 9.1 x 10(-6) cm/s for the standard rate constant for hydrogen oxidation. The similarity in mass-transfer coefficients calculated for protons and [Fe(CN)(6)](4-) ions suggests a proton-coupled electron-transfer mechanism for the [Fe(CN)(6)](4-)/[Fe(CN)(6)](3-) couple. The results of the above investigations could have direct technological relevance for deciding catalyst materials having redox compatibility with the polymer electrolyte, especially in the preparation of catalyst-coated membranes (wherein the fuel-cell catalyst is directly coated onto the polymer membrane instead of on the carbon support).

All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior

Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.

Imaging the stomatal physiology of somatic embryo-derived peanut leaves by scanning electrochemical microscopy - Parthasarathy, Meera; Singh, Shweta; Hazra, Sulekha; Pillai, Vijayamohanan K. (Analytical and Bioanalytical Chemistry, 2008)
The stomatal physiology, chlorophyll distribution and photosynthetic activity of somatic embryo (SE)- and seedling-derived peanut plants grown in vitro (test tube-grown) and extra vitrum (soil-grown) are investigated using scanning electrochemical microscopy (SECM). This SECM imaging is performed in two different feedback modes, corresponding to oxygen evolution and chlorophyll distribution. More specifically, the oxygen evolution profiles of the in vitro leaves indicate important differences in leaf anatomy between the SE- and seedling-derived leaves. On the other hand, the chlorophyll distribution images show individual stomata of size ca. 27 +/- 5 mu m. Further studies on senescing (aged) leaves reveal interesting voltammograms that vary widely over the stomatal complexes and the surrounding tissues, probably due to the release of electroactive metabolites during chlorophyll breakdown when the leaves turn yellow. Thus, the present investigation could open up new opportunities for characterizing botanical systems using electroanalytical techniques. In addition, it could provide further insights into various areas of current relevance, including signal transduction, cell fate/differentiation and developmental biology.
Keywords: leaf senescence; oxygen evolution; photosynthesis; SECM; somatic embryogenesis; stomata

Tuning the transport properties of Poly(oxyethylene)bisamine - Nafion polyelectrolyte complexes by dielectric manipulation - Parthasarathy, Meera; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Macromolecules, 2008)
Polyelectrolyte complexes (PECs) of Nafion-H+, a perfluorosulfonic acid ionomer, and Poly(oxyethylene)bisamine (Polyox) were synthesized, and the effect of electrostatic interactions on the physicochemical properties of the individual components was studied using a combination of spectroscopic and electrochemical techniques. More specifically, the pristine PECs were extensively characterized using viscosity, surface tension, and pH measurements and diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy and their transport properties were investigated using cyclic voltammetry and electrochemical impedance spectroscopy, by employing [Fe(CN)(6)](3-) as a redox probe. Acid-base interaction between Nafion and Polyox is evident from pH measurements of the blend solutions, which indicate salt formation at a 50:50 composition, supported further by the existence of a maximum in the plot of surface tension versus blend composition. DRIFT spectra of the PEC membranes indicate subtle changes in the ionic environment and a transition from a state of medium hydration to a partially dehydrated state of the parent ionomer, Nation, after complexation with Polyox. Further evidence for polyelectrolyte-polyelectrolyte association is obtained from cyclic voltammetry, which shows that the interaction between the redox active chromophore, [Fe(CN)(6)](3-), and the pendent sulfonate groups of Nafion is minimized by complexation with the oppositely charged polyelectrolyte Polyox. The water-soluble nature of these PECs along with the tunable range of properties with blend composition could qualify them as suitable candidates for developing stimuli-responsive polymer systems for pharmaceutical and environmental applications.

Domain size manipulation of perflouorinated polymer electrolytes by sulfonic acid-functionalized MWCNTs to enhance fuel cell performance - Kannan, Ramaiyan; Parthasarathy, Meera; Maraveedu, Sreekuttan U.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Langmuir, 2009)
The application of sulfonic acid-functionalized multiwalled (s-MWNT) carbon nanotubes to manipulate the hydrophilic domain size of Nafion membranes is explored here as an option for tuning the proton conductivity of polymer electrolyte membranes for hydrogen-oxygen fuel cells. The electrochemical impedance experiments provide preliminary evidence of increased proton conductivity, while small-angle X-ray scattering measurements line. out enhanced ionic cluster domain size in these composite membranes as the central reason for higher conductivity (70 angstrom for the optimum composite membrane vs 50 angstrom for Nafion 115) values. Scanning electrochemical microscopy indicates synergistic interaction between the sulfonic acid functional groups present in the Nation membrane and those on the nanotube surface. More interestingly, the nanotube-tailored Nafion membranes ameliorate the performance of fuel cells as confirmed by measurements at a sin le-cell level, which reveal a maximum power density of 380 mW cm(-2), higher than those of Nafion 115 (250 mW cm(-2)) and recast Nafion (230 mW cm-2) membranes. Thus, in addition to providing an elegant means of controlling the ionic cluster size, the strategic approach of using CNT both as an anchoring backbone for -SO(3)H groups to enrich proton conductivity and as a blending agent to improve the mechanical characteristics of the Nafion phase might be helpful in alleviating many critical problems associated with the use of commercial Nafion membranes.

Imaging hydrogen oxidation activity of catalyst-coated perfluoro sulfonic acid-polymer electrolyte membranes using scanning electrochemical microscopy - Parthasarathy, Meera; Pillai, Vijayamohanan K. (Journal of Chemical Sciences, 2009)
Scanning Electrochemical Microscopy (SECM) is a unique technique for studying fast heterogeneous kinetics and to map reactivity gradients along the surface of an electrocatalyst, especially when it involves multiple surface sites of varying reactivity. It combines the dual advantages offered by ultramicroelectrode (UME) voltammetry in terms of reduced ohmic drop and insignificant double layer charging contribution with the advantages of imaging by rastering the UME across an electro-active surface. In this work, we demonstrate these distinctive features of SECM in evaluating reactivity gradients on catalyst (Pt/C) coated NafionA (R) films towards hydrogen oxidation activity, a reaction of immense technological relevance. Imaging has been performed in the feedback mode by allowing H(2) evolution at the tip (25 A mu m Pt UME), which is reoxidized at the substrate electrode containing Pt/C-Nafion film. Interesting distribution in H(2) oxidation activity has been observed as a function of potential applied to the Pt/C-Nafion film. In addition, a plot of normalized tip current versus the substrate electrode potential indicates the effect of potential-induced reactivity change in the catalyst-coated membranes. The results of the present investigation are believed to be useful to H(2)/O(2) PEM fuel cells with respect to evaluating reactivity gradients of catalyst-coated polymer electrolyte membranes, which is important to rectify problems related to catalyst utilization.
Keywords: hydrogen oxidation; Imaging; Nafion; platinum; SECM

Bio-inspired catalyst compositions for enhanced oxygen reduction using nanostructured Pt electrocatalysts in polymer electrolyte fuel cells - Parthasarathy, Meera; Kannan, Ramaiyan; Sreekumar, Kurungot; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2010)
Composites of Nafion with a class of bio-molecules viz., plant hormones, are explored as potential polymer electrolytes for improving the proton transport inside the catalyst layer of a H(2)/O(2) fuel cell. Specifically, four nitrogenous plant hormones, two each from the class of auxins and cytokinins have been investigated, following preliminary characterization of the composite dispersions and membranes. Interestingly, the use of indole-3-acetic acid (an auxin) in the catalyst layer reveals a 30% enhancement in Pt catalyst utilization and improved fuel cell performance by 150 mW cm(-2). The effect of these bio-molecules on the kinetic and mass transport parameters has been analyzed systematically using a combination of electrochemical and spectroscopic techniques.

Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation